THE CORPORATE CRIME CASE ANALYSIS: CORRUPTION CRIMES AT THE MARITIME SECURITY AGENCY (BAKAMLA) RELATED TO SATELLITE AND DRONE PROCUREMENT INVOLVING PT. MERIAL ESA - Yosep Jadi Parlindungan Pasaribu; Surya Nita; Anggi Aulina Harahap (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
Corporations also play an important role in the flow of change and growth in the world economy. The existence of corporations is also related to control of natural resources and global finance However, it is not uncommon for corporations in their activities to commit deviant acts or crimes with various modus operandi. Crimes committed by corporations are often called corporate crimes. This research paper discusses one case of corporate crime that occurred in Indonesia. This is because the problem of corporate crime has recently become more common. One of them is related to a corruption case at the Bakamla, related to the procurement of satellites and drones involving PT Merial Esa. The verdict determined that PT Merial Esa was found guilty of breaching Article 5, paragraph (1), letter b of Republic of Indonesia Law Number 31 of 1999 on the Eradication of Corruption Crimes, as amended by Republic of Indonesia Law Number 20 of 2001, alongside violations of Article 55, paragraph (1), along with Article 64, paragraph (1) of the Criminal Code. In addition to the penalties, PT Merial Esa has been fined IDR 200 million and ordered to pay an additional compensation of IDR 126 billion. A significant challenge in addressing this matter has been the presence of an individual whose role remains unclear; their whereabouts are unknown, yet they are believed to be pivotal in illuminating this case. Moreover, the involvement of military personnel complicates matters further, as such cases necessitate specialized handling due to their unique regulations.